Costituzione, ieri e oggi - Nevola, Gaspare (SocietàMutamentoPolitica, 2023)
Constitutions represent an answer to a problem that derives from the nature of human beings and from their co-living together in a common social and political space. The root of the “constitutional problem” can be summed up with the following double question: how to create a stable and safe human/political community for zoon politikon, inside of a given territory, under a political organization flexible enough to adapt to internal and external changes which can threaten stability and security of collective coexistence? And how to do it between order and freedom, between power and law, between consent and dissent, between majority and minority? The present essay examines conceptual, empirical and historical profiles concerning the constitutional matter which has engaged the Ancients as well as the Moderns and Contemporaries. The essay emphasizes, on one side, the transformations of constitutions, on the other side, the intrinsic nature of constitutions in terms of “sociopolitical contract” and the normative telos that characterizes them. In contemporary societies, the Occidental ones in primis, the constitutional telos stay wrapped up, more than in the past, in an intimate (and conflictual) interweaving between formal (or encoded) constitution and “material” constitution “practiced” in social, cultural and political life. One might say that men do their constitutions, but not at will: systemic dynamics and structures (social and cultural, economics and technological, juridical and political) matter.